TRANSFORMING HOTS-ORIENTED LEARNING THROUGH PROBLEM-BASED LEARNING AMONG MADRASAH IBTIDAIYAH STUDENTS: A LITERATURE REVIEW - Muhammad Sofyan Atsauri; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Strengthening Higher Order Thinking Skills (HOTS) at the Madrasah Ibtidaiyah level is essential because basic education can no longer rely only on memorization, but must also develop students’ ability to analyze, evaluate, and create. This article aims to analyze the concept of implementing Problem-Based Learning (PBL) and its effectiveness in improving HOTS among Madrasah Ibtidaiyah students based on findings from previous studies. This study employed a literature review method using theoretical books, official documents, conceptual articles, classroom action research, and systematic reviews relevant to PBL, HOTS, and Islamic primary education. Data were collected through documentation and analyzed using content analysis through theme identification, classification of findings, comparison across literature, and synthesis. The review indicates that PBL is effective in improving HOTS when learning begins with contextual problems, followed by student organization, guided inquiry, solution presentation, and reflection on the learning process. The effectiveness of PBL is influenced by the quality of problems, teacher facilitation, group collaboration, student readiness, and the alignment of HOTS assessment. This article affirms that PBL can serve as a learning transformation strategy in Madrasah Ibtidaiyah that not only improves higher-order cognitive abilities but also develops students’ independence, collaboration, and responsibility